التجديد في التفسير: مفهومه - دواعيه - ضوابطه - أهدافه - بوحوش, غنية (جامعة الوادي - University of Eloued, 2022)
ملخص: حاول هذا المقال بيان ضرورة العناية بتجديد التفسير، كونه واحدا من العلوم الإسلامية الأكثر أهمية، لسيعه للكشف عن معاني القرآن الكريم، وعليه تنبني سائر العلوم، والمعارف، والآراء، والمذاهب. وهو بحاجة للتجديد، لقصوره عن الوفاء التام بحق القرآن الكريم، لمحدودية الطاقة البشرية. ولئن وجب التجديد في علم العقيدة، وعلم الفقه، وأصوله، فهو في علم التفسير أوجب، لأنه خَزَّان العلوم الإسلامية جميعا ومَدَدٌ لها كلها. وليؤتي التجديد أكله الطيب، ينبغي أن تنضبط حركته بجملة من الضوابط، تقيه التخبط والضلال. الكلمات المفتاحية: تجديد، التفسير، ضوابط، أهداف. Renovation in the qur'anic interpretation (tafsir): its concept - its reasons - its controls - its objectives Abstract This article attempts to indicate the necessity of renovation in the qur'anic interpretation (tafsir) since it is one the important islamic sciences, because it seeks to reveal the meanings of the Noble Qur'an, and upon it other sciences, opinions, cognitions, schools are established. It needs to be renovated due to the limited human efforts to fulfill Qur'an's right. If renovation is necessary in sciences like creed, jurisprudence (fiqh) and its principles (usul al-fiqh), then it is even more needed in quranic interpretation because it encompasses and supplies all islamic sciences. For the renovation to bear fruit, it has to adhere to some guidelines to protect it from confusion and deviance.
Renovation in the qur'anic interpretation (tafsir): concept , reasons , controls and its objectives
مقال
Keywords: تجديد ; التفسير ; ضوابط ; أهداف; Renewal; interpretation; controls; goals